THE FUTURE OF ENTERPRISE AUTOMATION: AI AS A TRANSFORMATIVE FORCE - Sravanthi Gopala (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
This research article examines the transformative impact of artificial intelligence on enterprise automation across various industries. The article investigates how AI-powered solutions are revolutionizing traditional business operations, from manufacturing and customer service to financial services and healthcare. It analyzes the current state of enterprise automation, exploring the transition from conventional rule-based systems to intelligent automation frameworks. The article also discusses key technologies driving this transformation, including machine learning, deep learning, natural language processing, and cognitive automation. Furthermore, it examines implementation challenges, technical infrastructure requirements, data quality considerations, and skills development needs. The article concludes by exploring future trends and opportunities in hyper automation, edge computing, IoT integration, and autonomous systems development, providing insights into the evolving landscape of enterprise auto